PENENTUAN SIFAT TERMOFISIK MAHKOTA DEWA (THERMAL PROPERTIES OF Phaleria macrocarpha) - Manalu, Lamhot P. (Badan Pengkajian dan Penerapan Teknologi, 2011)
of information on their thermal properties. Although a lot of experimental data can be found, the variety of products and the differences in measurement method make limitation on the value of the available data, especially for Indonesia’s products. These data are needed to get information about temperature change when a product was processed by heating or cooling. The data are important for optimizing the efficiency of energy used in the process. The objective of this study is to determine thermal diffusivity and conductivity of mahkota dewa or crown of god (Phaleria macrocarpha). The values were determined numerically with indirect methods. The result shows that thermal conductivity of mahkota dewa is 0.1359 W/moC, while its thermal diffusivity is 4.11x10-8 m2/s.